1998
DOI: 10.1161/01.hyp.32.2.280
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Bax Protein and Enhanced Apoptosis in the Left Ventricle of Spontaneously Hypertensive Rats

Abstract: Abstract-An association of increased apoptosis with overactivity of the local angiotensin-converting enzyme has been reported in cells from the left ventricle of adult rats with spontaneous hypertension (SHR). To gain insight into the regulation of cardiac apoptosis in arterial hypertension, we investigated the expression of the proteins Bcl-2 (an inhibitor of apoptosis) and Bax (an inducer of apoptosis) in the left ventricle of 30-week-old normotensive Wistar-Kyoto rats (WKY), SHR, and SHR treated with the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 41 publications
9
112
3
Order By: Relevance
“…Medical treatment did not significantly differ between patients with and without elevated cTnT in the present study. Experimental studies have shown that the long-term administration of an angiotensin-converting enzyme inhibitor (ACE-I) or an angiotensin II receptor blocker (ARB) prevents cardiomyocyte apoptosis in spontaneously hypertensive rats, 32,33) which suggests that either ACE-I or ARB can suppress ongoing myocardial damage. Further investigation is required to determine the mechanism of ongoing myocardial damage and its treatment in hypertensive patients.…”
Section: Therapeutic Implications Of Ongoing Myocardial Damage In Hy-mentioning
confidence: 99%
“…Medical treatment did not significantly differ between patients with and without elevated cTnT in the present study. Experimental studies have shown that the long-term administration of an angiotensin-converting enzyme inhibitor (ACE-I) or an angiotensin II receptor blocker (ARB) prevents cardiomyocyte apoptosis in spontaneously hypertensive rats, 32,33) which suggests that either ACE-I or ARB can suppress ongoing myocardial damage. Further investigation is required to determine the mechanism of ongoing myocardial damage and its treatment in hypertensive patients.…”
Section: Therapeutic Implications Of Ongoing Myocardial Damage In Hy-mentioning
confidence: 99%
“…Interestingly, losartan also blocked stretch-induced apoptosis in cultured adult cardiomyocytes (Leri et al, 1998) suggesting that the Gq-coupled AT1 receptor mediates activation of apoptotic pathways by mechanical stretch. Several studies have shown that ACE inhibitors or AT receptor antagonists also block the cardiomyocyte apoptosis observed in spontaneously hypertensive rats Goussev et al, 1998;FortunÄ o et al, 1998).…”
Section: Gaq Signaling In Apoptosis and Failurementioning
confidence: 99%
“…Cardiomyocytes were distinguished from nonmyocytes by microscopic appearance; that is, well-shaped, elongated, and striated cells. 16 …”
Section: Histological Analysismentioning
confidence: 99%
“…5 AT 2 R has been shown to mediate induction of apoptosis in the PC12 cell line, 6 vascular smooth muscle cells, 7 vascular endothelium, 8 fibroblasts, 9 granulose cells in the rat ovary, 10 neurons from the rat brain, 11 and human fetal adrenal cells. 12 Recently, it has been reported that cardiac remodeling in various heart diseases involves a loss of cardiomyocytes due to apoptosis [13][14][15] and that Ang II stimulation induces cardiomyocyte apoptosis in vivo 13,14,16 and in vitro. [17][18][19] Ligandbinding experiments 1 indicated that AT 2 R as well as AT 1 R is expressed in the heart and that AT 2 R subtype is upregulated in the diseased heart.…”
mentioning
confidence: 99%